Affecttive Development of Children Due to Anxiety During Pregnancy : A Literature Review - Qurniati, Nina; Erye Frety, Endyka (Universitas Airlangga, 2025)
Given its potential to affect the growing fetus, maternal mental health during pregnancy is essential. Anxiety during pregnancy is associated with the socio-emotional development of the child, potentially resulting in behavioral and emotional issues in the future. Children of mothers who experience anxiety during pregnancy are predicted to experience poorer growth and development in infancy and preschool age. This study aims to determine the effects of anxiety during pregnancy. This study used a literature review approach from 8 relevant articles from the online databases Scopus, PubMed, Google Scholar, and Garuda. The inclusion criteria of this study were original research in Indonesian or English, respondents measured anxiety during pregnancy, and measurement of infant/child affective patterns, which were fully accessible. The findings indicated that a child’s affective development and anxiety during pregnancy are significantly correlated. It can be characterised by decreased attention to facial expressions in infants crying, sleeping, and feeding. In addition, the child may experience impaired socio-individual neurodevelopment, fine motor and emotional development, and poorer language. This can lead to negative behavioral development, such as hyperactivity and emotional disturbances, from preschool to adulthood. The more often and longer the mother experiences anxiety, the more likely the child is to have emotional and behavioral disorders.